The amathiiform Ctenostomata (phylum Bryozoa) of New Zealand —including four new species, two of them of probable alien origin - Gordon, Dennis P.; Spencer-Jones, Mary (Zootaxa, 2013)
The status of the vesiculariid ctenostome genus Amathia in New Zealand has been evaluated on the basis of all known material, including historic specimens in museums and those newly collected during formal surveillance of ports, harbours and vessels for possible alien species. Eight species are recognised, four of them new to science. Amathia gracei n. sp. and Amathia zealandica n. sp. are the only apparently endemic species. Amathia chimonidesi n. sp. appears to be a pre-viously unrecognised alien species and is known only from shipping harbours and/or yacht marinas and some nearby beaches. Amathia similis n. sp. has been known in the Auckland area since the 1960s but was confused with A. distans Busk. Amathia bicornis (Tenison-Woods), A. biseriata Krauss, A. lamourouxi Chimonides and A. wilsoni Kirkpatrick are Australasian species that occur naturally on both sides of the Tasman Sea. Of this latter group, A. bicornis was discovered only at a single locality on the southwest coast of North Island in 1983 on a fucoid seaweed and it may be relatively re-cently self-introduced. A specimen of A. lendigera (Linnaeus) in the Museum of New Zealand, purportedly from Napier, is considered to be based on a misunderstanding or a labelling error and does not represent a failed alien introduction. The Amathia-like vesiculariid Bowerbankia citrina (Hincks) sensu lato is newly recorded for New Zealand. Keys are provided to the amathiiform (i.e. Amathia and Amathia-like) Ctenostomata of New Zealand and to the worldwide species of Ama-thia and Bowerbankia with zooid clusters spiralled on stoloniform axes.